2020
DOI: 10.1111/1365-2478.12920
|View full text |Cite
|
Sign up to set email alerts
|

An efficiency‐improved genetic algorithm and its application on multimodal functions and a 2D common reflection surface stacking problem

Abstract: A B S T R A C TAlthough Genetic Algorithms have found many successful applications in the field of exploration geophysics, the convergence speed remains a big challenge as Genetic Algorithms usually require a huge amount of fitness function evaluations. In this paper, we propose an efficiency-improved Genetic Algorithm, which has both a good global search capability and a good local search capability, and is also capable of robustly handling the premature convergence challenge commonly seen in linear and direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Several performances of the method were evaluated by experiments. The comparison results demonstrated that this algorithm has excllent performance and its prediction accuracy reaches 98.6% [17].…”
Section: Related Workmentioning
confidence: 95%
“…Several performances of the method were evaluated by experiments. The comparison results demonstrated that this algorithm has excllent performance and its prediction accuracy reaches 98.6% [17].…”
Section: Related Workmentioning
confidence: 95%
“…It can improve the extensive search ability of the algorithm in the solution space and reduce the dependence on the initial solution, thus effectively avoiding the problem of falling into the local optimal solution and being unable to find the global optimal solution. a) Design of chromosome coding: The dimension of the chromosome gene vector in real coding is determined by the number of weights and thresholds present in the backpropagation neural network [22], and the formula is as follows:…”
Section: ) Optimization Of Back-propagation Neural Network Algorithmmentioning
confidence: 99%
“…There are at least two types for each genetic operator, and their combination with each other can give various results. An attempt to pick better parameters was made in the [11], where the authors created their own program, but the result can differ depending on the assigned task. The present study aims to determine the optimal parameters of the genetic algorithm for doctors in the task of an individualized treatment strategy search.…”
Section: Analysis Of the Latest Research And Publicationsmentioning
confidence: 99%
“…As a result, a new individual is obtained, which contains information about its ancestors. There are many types of individual crossover [11].…”
Section: Fig 1 Flowchart Of Genetic Algorithmmentioning
confidence: 99%